Host–guest chemistry of giant molecular shape amphiphiles based on POSS–PDI conjugates. Issue 7 (17th February 2021) - Chen, Jia; Lin, Heng-Yi; Ji, Xiaohuan; Zhao, Haoru; Sun, Bin; Wang, Chien-Lung; Zhu, Meifang
Abstract : Giant shape amphiphiles (GSA) are giant molecules made with nano-building blocks that have distinct shapes. Abstract : Giant shape amphiphiles (GSA) are giant molecules made with nano-building blocks that have distinct shapes. The incompatible packing behaviors of the nano-building blocks of GSA could create cavities within certain conformers of the GSA, but the host–guest chemistry of GSA has not been explored yet. In this study, POSS-PDI-POSS (PPP ), which is made by connecting two nano-cubes, isobutyl-polyhedral oligomeric silsesquioxanes (POSS), to a conjugated π-conjugated core, perylene diimide (PDI), is demonstrated as a novel acyclic synthetic host. In its bent conformer, PPP shows a cavity next to its PDI core. Via forming host–guest complexes with π-conjugated guests such as pyrene and perylene, PPP is found to transform from the bent-conformer into the extended-conformer, creating the steric features to accommodate guest molecules. Subsequent thermal annealing of the host–guest complexes removes the π-conjugated guests and restores the bent conformation and photophysical properties of PPP, which verifies that PPP, as a novel acyclic host, is capable of dynamic host–guest assembly. Moreover, the results prove that cavities at the molecular level can be created by connecting nano-building blocks with distinct shapes. This finding may inspire developments in the host–guest chemistry of GSA and nanomaterial innovation.